Single-cell transcriptomics reveals immune remodeling of the murine lung microenvironment following chronic house dust mite exposure - Chang, Han; Zeng, Liping; Malakoutikhah, Zahra; Nasamran, Chanond A.; Herdman, Scott; Corr, Maripat; Fisch, Kathleen M.; Webster, Nicholas J. G; Raz, Eyal; Bertin, Samuel (Frontiers in Immunology, 2025)
IntroductionHouse dust mite (HDM) is a common environmental aeroallergen strongly associated with asthma and chronic airway inflammation. While HDM exposure is known to induce T helper 2 (Th2)-mediated eosinophilic inflammation, its chronic effects on interleukin-1β (IL-1β)-associated neutrophilic inflammation remain poorly understood. This study used single-cell RNA sequencing (scRNA-seq) to investigate how chronic HDM exposure remodels the murine lung immune microenvironment, with a focus on the role of IL-1β in shaping HDM-driven immune responses.MethodsWild-type and Il1b-deficient mice on a C57BL/6 background were subjected to chronic HDM exposure over a 5-week period, and scRNA-seq was performed to characterize changes in the lung immune landscape. To enhance resolution of specific cell populations and better define their functional states, we performed subclustering, followed by pathway enrichment and transcription factor activity analyses. To account for endotoxin-dependent variability in HDM extracts, scRNA-seq was conducted using a low-lipopolysaccharide (LPS) HDM extract, while validation studies (histopathology, RT-qPCR, ELISA, and immunofluorescence) were performed using a high-LPS HDM extract.ResultsOur analysis demonstrates that chronic HDM exposure promotes the recruitment and activation of diverse immune cell populations in the lungs, including neutrophils, M2-polarized macrophages, B-2 (follicular) B cells, and multiple subsets of regulatory and effector CD4⁺ T cells. These populations contribute differently to the development or resolution of chronic lung inflammation through IL-1β-dependent and -independent mechanisms. scRNA-seq indicated that IL-1β signaling is critical for sustaining neutrophil and Th17 responses, whereas Il1b deficiency promotes Th2-skewed polarization. Validation experiments revealed that these effects are influenced by the endotoxin content of HDM extracts, which can override genotype-dependent effects.DiscussionThese findings demonstrate that chronic HDM exposure profoundly remodels the lung immune microenvironment through IL-1β-dependent and -independent mechanisms. The effects are context-dependent and modulated by the endotoxin content of HDM extracts, highlighting the complex immunomodulatory effects of HDM in inducing chronic lung inflammation.